Microbeads in facial scrubs: a study on university students’ perception and participation - Aqilah Zubir (2021)
Microbeads is one of the well-known particles among microplastic sub-categories that becomes dangerous towards environment including marine ecosystem. All the original and traditional substances where it is biodegradable alternatives are replaced over these years by a non-biodegradable, cheap, tiny plastic particle which is called microbead. The pollution that caused by microbead particles from the personal care products such as facial scrubs has been well established around the world and leads a concern at local, regional, national and global levels due to the adverse effects towards aquatic marine ecosystem. Students that basically consists of young generation plays crucial role in reducing the occurrence of microbead particles in marine ecosystem since they probably be the one that will prevent the microbeads pollution happen in future years. Hence, students’ perception needs to be understood to help reduce the microbeads pollution. Therefore, this study analysed perception of 365 female students from University Malaysia Kelantan regarding the microbead particles in facial scrubs by conducted survey that consist of three sections of questionnaire survey. The data then was analysed by using Statistical Package for the Social Science (SPSS). The female students were chose because skincare has always been associated with female. Most of female students had bad perception regarding microbeads particles and its pollution towards marine ecosystem. This study also analysed the students’ participation in the future in reducing the occurrence of microbead pollution in marine ecosystem. From the study, it showed that younger people appear to have a higher understanding and knowledge of the use of microbeads in personal care products.